2015
DOI: 10.21608/bvmj.2015.31703
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological status of meat and chicken received to University student hostel

Abstract: A grand total of 60 random samples of chicken and meat (30 of each) before and after cooking (n=15 of each) of both type was collected from a university student hostel, Egypt for microbiological examination. The average values of aerobic plate count and anaerobic count (cfu/g) were 5.4x10 4 ±7.9x10 3 and 2.6x10 4 ±4.4x10 3 for raw meat, 3.6x10 4 ±2.1x10 3 and 2.2x10 4 ±3.8x10 3 for raw chicken meat ,1.2x10 4 ±1.9x10 3 ,1.3x10 4 ± 4.9x10 3 for cooked meat and 1.9x10 4 ±2.2x10 3 & 1.3x10 4 ±4.9x10 3 cfu/g for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Our results near to that recorded by ( Mahmoud and Hamouda-Seham, 2006) who tested 80 random samples of poultry thigh and breast (40 of each) collected from El-Gharbia governorate and revealed that the mean values of APC (cfu/g) were 1.4 x10 6 ± 4 x10 5 and 6 x10 5 ± 2 x10 4 , respectively. Higher results were reported by Oumokhtar (2000) who recorded that the mean value of APC in chicken meat was 2, 9 x 10 4 cfu/g and higher than that recorded by (Shaltout et al, 2015) who recorded that the mean value of APC in raw chicken meat was 3.6x10 4 ±2.1x10 3 . The prevalence of Salmonella spp.…”
Section: Discussionmentioning
confidence: 61%
“…Our results near to that recorded by ( Mahmoud and Hamouda-Seham, 2006) who tested 80 random samples of poultry thigh and breast (40 of each) collected from El-Gharbia governorate and revealed that the mean values of APC (cfu/g) were 1.4 x10 6 ± 4 x10 5 and 6 x10 5 ± 2 x10 4 , respectively. Higher results were reported by Oumokhtar (2000) who recorded that the mean value of APC in chicken meat was 2, 9 x 10 4 cfu/g and higher than that recorded by (Shaltout et al, 2015) who recorded that the mean value of APC in raw chicken meat was 3.6x10 4 ±2.1x10 3 . The prevalence of Salmonella spp.…”
Section: Discussionmentioning
confidence: 61%
“…The symptoms the symptoms of salmonellosis include diarrhoea, nausea, vomiting, fever and abdominal cramps [22]. The results in Tables 9 and 10 reported that staph .aureus was isolated from20% of meat,40%of meat kofta,33.33%of chicken and 46.67%of chicken kofta .such organism was isolated previously from ready to eat meat meals by [19,21] who isolated staph aureus from cooked samples the presence of staph .aureus in RTE meat meals may be due to their contamination from food handlers, bad cleaned equipment's or post processing contamination [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella microorganisms were previously isolated from cooked meat meals also salmonella failed to be isolated from cooked meat meals. The symptoms the symptoms of salmonellosis include diarrhea, nausea, vomiting, fever and abdominal cramps [15][16][17][18][19][20][21][22][23][24][25]. The results in Tables 9&10 reported that staph.…”
Section: Discussionmentioning
confidence: 99%